मेरो सम्झनामा : डा. ग्रेगोरी ग्याब्रियल मास्कारिनेक - Poudel, Keshav Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2023)
This paper describes the interaction and understanding with Professor Gregory G. Maskarinec.